2009
DOI: 10.1037/a0013991
|View full text |Cite
|
Sign up to set email alerts
|

Multiple learning parameters differentially regulate olfactory generalization.

Abstract: Sensory representations depend strongly on the descending regulation of perceptual processing. Generalization among similar stimuli is a fundamental cognitive process that defines the extent of the variance in physical stimulus properties that becomes categorized together and associated with a common contingency, thereby establishing units of meaning. The olfactory system provides an experimentally tractable model system in which to study the interactions of these physical and psychological factors within the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
81
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(86 citation statements)
references
References 55 publications
1
81
0
Order By: Relevance
“…That is, there is no reason that the pattern of functional lateral inhibitory weights should reflect the similarity of OSN receptive fields as measured within any one particular statistical odor environment. Rather, it has been hypothesized that decorrelation in this layer reflects olfactory learning, altering the behavioral discrimination of similar odorants based on individual experience (Cleland et al, 2009; Cleland, 2010). …”
Section: Discussionmentioning
confidence: 99%
“…That is, there is no reason that the pattern of functional lateral inhibitory weights should reflect the similarity of OSN receptive fields as measured within any one particular statistical odor environment. Rather, it has been hypothesized that decorrelation in this layer reflects olfactory learning, altering the behavioral discrimination of similar odorants based on individual experience (Cleland et al, 2009; Cleland, 2010). …”
Section: Discussionmentioning
confidence: 99%
“…Honeybees generalize their responses across perceptually distinct binary mixtures of floral odorants after learning that each leads to the same rewarding outcome [29]. Rodents trained to dig for a reward in response to an odor cue generalize toward structurally similar odorants depending on the saliency and strength of associative learning [30]. Both of these studies underscore the importance of behavioral contingency for category formation.…”
Section: Odor Categorization: Lumping Not Splittingmentioning
confidence: 99%
“…To date, it was commonly suggested that configural processing of odour mixture greatly rely on experience and memory (e.g. Staubli et al, 1987;Cleland et al, 2009). For instance, Wilson and Stevenson (Wilson and Stevenson, 2003) proposed that prior experience with an odour could be a condition to perceive complex mixtures of odorants through a strong synthetic (configural) processing and in the meantime to display strong elemental figure-ground discrimination.…”
Section: G Coureaud and Othersmentioning
confidence: 99%